Performance of a horizontal axis marine current turbine– A comprehensive evaluation using experimental, numerical, and theoretical approaches. (1st April 2018) - Rahimian, Masoud; Walker, Jessica; Penesis, Irene
Abstract: This study provides a comprehensive assessment of a 2 bladed horizontal axis marine current turbine using experiments on two scale models, compared to both theoretical and numerical models and previous experiments in other facilities. The experiments were performed in a towing tank and a circulating water channel on rotors of 500 mm and 800 mm diameter. The effect of model scale was investigated together with facility bias. The impact of facility bias on the performance assessment was found to be induced from blockage and the presence of a shear flow velocity profile in the circulating water channel. A BEM model was modified to consider shear velocity profile in the performance calculations. No significant changes were seen in the BEM model results by inserting the shear flow in the code. In addition, the QBlade software was employed as a tool to investigate the effect of Reynolds number. It can provide the performance outcomes for a range in which the results are sensitive to Reynolds number. A RANS CFD model was provided which simulates the turbine in steady flow conditions. The theoretical, numerical and physical models were used to study the effect of scaling. The BEM and CFD model both had good agreement with the experimental results, which provides a strong platform for more detailed study on the HAMCT hydrodynamics. Highlights: Experiments were performed on two scale models in two hydrodynamic facilities. Scale effect and facility bias were studied using experimental results. A BEM model and a RANS model were developed for the turbine performance assessment. BEM and experimental results showed negligible effect of shear on mean power output. Experiments, theory and CFD yielded similar outcomes on scale/Reynolds number effect.